The Role of Generative Artificial Intelligence (GenAI) in Enhancing Self-Learning and Developing Employees’ Digital Skills: An Applied Study in the Oil Products Distribution Authority in the Middle Euphrates Region - Baqer Ali Balchat (Research Parks Publishers, 2026)
Research aims to study role intelligence artificial genital (GenAI) in strengthening learning self and development skills digital have employees, from during research applied in body distribution products oil in euphrates the middle it starts. The problem research from presence gap note in level skills digital have some employees, weakness accreditation on methods learning self modern, which limits from effectiveness programs development job traditional. It is assumed that employment technologies intelligence artificial obstetric, like models linguistic Interactive, maybe that contributes in to improve abilities employees via to provide environment to learn flexible interactive it depends on Guidance Immediate, and simplification concepts administrative and technology, Presentation content its training custom according to needs the learner adopted. Search curriculum descriptive analytical, with application tool questionnaire on sample from employees the authority addition to Interviews with some officials in units training and development. It includes analysis measurement level awareness with intelligence artificial, and extent use its tools in learning self, and impact that on development Skills digital like use applications office, and management data, and dealing with Systems electronic and from expected that show results presence relationship positive between use tools GenAI and increase efficiency learning self please on to improve clear in level skills digital have the employees. As well Seeks Search to presentation model applied maybe Its adoption inside the foundation to merge intelligence artificial in Programs training and development continuous and concludes Search to that intelligence artificial obstetric it represents tool strategy effective to support transformation digital in Institutions governmental, provided availability environment organizational supportive and policies clear Include usage optimum for this technologies.